Comprehensive assessment of Erwinia amylovora: from establishment risk in global host production areas to dispersal dynamics and associated economic losses in China - Li, Ming; Xian, Xiaoqing; Jin, Zhenan; Qi, Yuhan; Guo, Jianyang; Yang, Nianwan; Zhang, Guifen; Xu, Jin; Liu, Wanxue (Frontiers in Plant Science, 2026)
Erwinia amylovora is the bacterial pathogen that causes fire blight and is considered one of the most important plant pathogenic bacteria in the world, posing a serious threat to pear and apple production. However, majority of the current risk assessment studies have focused primarily on the potential geographic distribution of E. amylovora, with less focus on its dispersal patterns, dispersal risk areas, and economic impacts. Here, species distribution models, the minimum cost arborescence approach, the MigClim package, and Monte Carlo stochastic simulations were integrated to comprehensively assess the global establishment risk, the local dispersal patterns, the dispersal risk areas, and the economic losses for E. amylovora. The results showed that E. amylovora is primarily distributed in North America, southern South America, Europe, northern and southern Africa, western and eastern Asia, and southern Oceania under near-current climatic conditions. In addition, the overlapping area between the distribution area of E. amylovora and the host production area is 1,897.62 × 104 km2, mainly located in central North America, southern South America, Europe, northern Africa, eastern and western Asia, and southern Oceania. Its global distribution and the overlapping areas are expected to expand further under future climatic conditions. Erwinia amylovora shows a primarily “leap-frog” long-distance spread in China, and the dispersal risk area is mainly in northwestern China. The economic losses caused by E. amylovora to the host industry amounted to 5,603.66 million dollars without any control measures; however, 2,390.13 million dollars can be saved after control measures. Such comprehensive risk assessments provide global guidance for the monitoring and control of E. amylovora in host production areas while also helping to formulate management priority strategies in local dispersal risk areas, thereby reducing economic impacts.